Pattern of Ear Nose and Throat (Ent) Diseases Seen by Otorhinolarynologist at Bishop Sanahan Specialist Hospital Out Patient Clinics, Nsukka South East Nigeria - Anekpo, Chijioke C.; Modebe, Emmanuel O (Jour Med Resh and Health Sci, 2022)
Ear nose and throat(ENT) diseases are serious public health concern affecting patients of all ages in both rural and urban centers. The study aimed to determine the pattern of ENT diseases at Bishop Sanahan Specialist Hospital Nsukka, South East Nigeria Material and Method This is a descriptive retrospective study conducted in outpatient clinics of Bishop Sanahan Specialist Hospital Nsukka, South East Nigeria. A total of 396 patients treated by visiting otorlaryngologist from March to February 2020 were included in the study. The data were extracted from the patient's folder and all analyzed statistically using SPSS version 21 Result In this study a total of 396 patients were seen, male 169 patients (42•7%) and female 227 patients (57•3%) with a mean age of >35yrs.Ear diseases were mostly seen (73%) followed by throat (14•6%) and nose (11•6%) respectively. Cerumen auris was the most treated ear problem while chronic tonsillitis and allergic rhinosinusitis occurs more in the throat and nose respectively. However hearing loss, rhinitis, laryngitis and sinonasal tumours were associated with old age group(>60)years. Conclusion. There is need to created awareness of the common ENT diseases in Nsukka Local Government Area and beyond. This will help to reduce the burden of disease in the community.